Strategi Branding Donat Pinkan Mambo dalam Meningkatkan Minat Beli Konsumen melalui TikTok - Danny Christiawan; Rini Darmastuti; Deasy Carolina (Institut Agama Hindu Negeri Gde Pudja Mataram, 2026)
Digital transformation has reshaped the marketing landscape, establishing TikTok as a crucial platform for brand identity development through intensive digital narratives. This research aims to analyze the branding strategy of Donat Pinkan Mambo in increasing consumer purchase intention via TikTok. The method employed is qualitative descriptive with a Qualitative Content Analysis approach focusing on live streaming content and digital interactions. The results indicate that the integration of personal vulnerability narratives with TikTok’s interactive features successfully creates strong brand differentiation. The